Frontispiece: A Highly Reactive Oxoiron(IV) Complex Supported by a Bioinspired N3O Macrocyclic Ligand. Issue 46 (8th November 2017) - Monte Pérez, Inés; Engelmann, Xenia; Lee, Yong‐Min; Yoo, Mi; Kumaran, Elumalai; Farquhar, Erik R.; Bill, Eckhard; England, Jason; Nam, Wonwoo; Swart, Marcel; Ray, Kallol
Abstract : Iron Oxo Complexes In their Communication onpage 14384 ff., W. Nam, M. Swart, K. Ray, et al. show that the oxoiron(IV) center in [Fe IV (O)(TMCO)(OTf)] + (bottom right) with an N3 O environment is significantly more reactive than that in [Fe IV (O)(TMC)(CH3 CN)] 2+ (top left) with an N4 environment.